2008
DOI: 10.1074/jbc.m802996200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Extrusion through the Cytoplasmic Vacuoles during Cell Death

Abstract: Under various conditions, noxious stimuli damage mitochondria, resulting in mitochondrial fragmentation; however, the mechanisms by which fragmented mitochondria are eliminated from the cells remain largely unknown. Here we show that cytoplasmic vacuoles originating from the plasma membrane engulfed fragmented mitochondria and subsequently extruded them into the extracellular spaces in undergoing acute tumor necrosis factor ␣-induced cell death in a caspase-dependent fashion. Notably, upon fusion of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 29 publications
1
72
0
Order By: Relevance
“…Nakajima et al have reported that fragmented mitochondria in MEFs deficient in CFLAR/c-flip (cflar ¡/¡ MEFs) are released through a mechanism mediated by an endocytosis-exocytosis pathway during the course of apoptosis elicited by TNF. 46 However, the autophagy machinery has proved not to be involved in this case, as 3MA has no effect. 46 To the best of our knowledge, our report is the first to demonstrate mitochondrial extrusion from LPS-stimulated cells through the autophagy machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakajima et al have reported that fragmented mitochondria in MEFs deficient in CFLAR/c-flip (cflar ¡/¡ MEFs) are released through a mechanism mediated by an endocytosis-exocytosis pathway during the course of apoptosis elicited by TNF. 46 However, the autophagy machinery has proved not to be involved in this case, as 3MA has no effect. 46 To the best of our knowledge, our report is the first to demonstrate mitochondrial extrusion from LPS-stimulated cells through the autophagy machinery.…”
Section: Discussionmentioning
confidence: 99%
“…46 However, the autophagy machinery has proved not to be involved in this case, as 3MA has no effect. 46 To the best of our knowledge, our report is the first to demonstrate mitochondrial extrusion from LPS-stimulated cells through the autophagy machinery. Recent research has indicated that the final point of autophagy is not always lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Considering recent reports that mitochondria are expulsed in early apoptosis (53) and that mtDNA stimulates either TLR9 in inflammation and transplant rejection (49,50) or, alternatively, the AIM2 inflammasome and/ or caspase-1 in sepsis (51), we initially argued that the pronounced immunostimulatory activity of MMP DNA could be attributed to selective accumulation of mtDNA in MMP derived from apoptotic cells (Fig. 5A).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nakajime et al found that fragmented mitochondria were sequestered in vacuoles that originated from the plasma membrane in cultured c-flip−/− mouse embryonic fibroblasts undergoing apoptosis [78]. These vesicles fused with the plasma membrane, resulting in the release of naked mitochondria into the extracellular space.…”
Section: Exocytosis/mitoptosismentioning
confidence: 99%